Physiologically Relevant Fluid-Induced Oscillatory Shear Stress Stimulation of Mesenchymal Stem Cells Enhances the Engineered Valve Matrix Phenotype - Gonzalez, Brittany A.; Perez-Nevarez, Manuel; Mirza, Asad; Perez, Marcos Gonzalez; Lin, Yih-Mei; Hsu, Chia-Pei Denise; Caobi, Allen; Raymond, Andrea; Gomez Hernandez, Mario E.; Fernandez-Lima, Francisco; George, Florence; Ramaswamy, Sharan (Frontiers in Cardiovascular Medicine, 2020)
Support of somatic growth is a fundamental requirement of tissue engineered valves. However, efforts thus far have been unable to maintain this support long-term. A key event that will determine the valve’s long-term success is the extent to which healthy host tissue remodeling can occur on the valve soon after implantation. The construct’s phenotypic-status plays a critical role in accelerating tissue remodeling and engineered valve integration with the host via chemotaxis. In the current study, human bone-marrow derived mesenchymal stem cells were utilized to seed synthetic, biodegradable scaffolds for a period of 8-days in rotisserie culture. Subsequently cell-seeded scaffolds were exposed to physiologically-relevant oscillatory shear stresses (overall mean, time-averaged shear stress ~ 7.9 dynes/cm2; overall mean, oscillatory shear index ~0.18) for an additional 2-weeks. The constructs were found to exhibit relatively augmented endothelial cell expression (CD31; compared to static controls) but concomitantly served to restrict the level of the activated smooth muscle phenotype (alpha-SMA) and also produced very low stem cell secretion levels of fibronectin (p<0.05 compared to static and rotisserie controls). These findings suggest that fluid-induced oscillatory shear stresses-alone are important in regulating a healthy valve phenotype of the engineered tissue matrix. Moreover, as solid stresses could lead to increased alpha-SMA levels, they should be excluded from conditioning during the culture process owing to their associated potential risks with pathological tissue remodeling. In conclusion, engineered valve tissues derived from mesenchymal stem cells revealed both a relatively robust valvular phenotype after exposure to physiologically-relevant scales of oscillatory shear stress, and may thereby serve to accelerate healthy valve tissue remodeling in the host post-implantation.